2022
DOI: 10.1038/s41467-022-32557-w
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative decomposition mechanisms of lithium carbonate on carbon substrates in lithium battery chemistries

Abstract: Lithium carbonate plays a critical role in both lithium-carbon dioxide and lithium-air batteries as the main discharge product and a product of side reactions, respectively. Understanding the decomposition of lithium carbonate during electrochemical oxidation (during battery charging) is key for improving both chemistries, but the decomposition mechanisms and the role of the carbon substrate remain under debate. Here, we use an in-situ differential electrochemical mass spectrometry-gas chromatography coupling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 56 publications
0
70
0
Order By: Relevance
“…Actually, the air contaminations (e.g., moisture and CO 2 ) will result in some insulating species (such as metal hydroxides and metal carbonates) at the cathode, which seriously deteriorates the round-trip efficiency, reaction reversibility, and cycling stability of MABs. 452,[501][502][503][504] In understanding the specific impact of contaminations on the performances of MABs, it was found that CO 2 can be used alone as the reactant gas (3CO 2 + 4M x+ + 4xe À -2M 2 CO 3 + C), i.e. metal-CO 2 batteries (MCBs).…”
Section: Batteriesmentioning
confidence: 99%
“…Actually, the air contaminations (e.g., moisture and CO 2 ) will result in some insulating species (such as metal hydroxides and metal carbonates) at the cathode, which seriously deteriorates the round-trip efficiency, reaction reversibility, and cycling stability of MABs. 452,[501][502][503][504] In understanding the specific impact of contaminations on the performances of MABs, it was found that CO 2 can be used alone as the reactant gas (3CO 2 + 4M x+ + 4xe À -2M 2 CO 3 + C), i.e. metal-CO 2 batteries (MCBs).…”
Section: Batteriesmentioning
confidence: 99%
“…In 2022, Cao et al used 1 M LiTFSI-tetraglyme as the electrolyte to quantify the gas evolution during the electrochemical oxidation of Li 2 CO 3 on carbon substrates using isotope labeling and in situ differential electrochemical mass spectrometry-gas chromatography system. 70 Initially, they labeled Li 2 13 CO 3 with 13 C isotope and found that Li 2 CO 3 only decomposed into 13 CO 2 without the formation of CO and O 2 through qualitative analysis, which means that carbon does not directly participate in the decomposition of Li 2 CO 3 . The DMA probe only reacted with 1 O 2 to generate a DMA-O 2 signal, which confirms that the oxygen in Li 2 CO 3 is released in the form of highly active 1 O 2 .…”
Section: Electrochemical Decomposition Of C and Li 2 Comentioning
confidence: 99%
“…Due to the high content of Ni 3+ (high oxidation ability) in the high-Ni NCM cathode (e.g., LiNi 0.8 Co 0.1 Mn 0.1 O 2 , NCM811), surface impurity (LiOH/Li 2 O/Li 2 O 2 /LiHCO 3 ) can rapidly react with CO 2 /O 2 /H 2 O to form Li 2 CO 3 during ambient-air storage, , which influences the performance of the NCM cathode (distorted structure, aggravated CO 2 evolution, , and unstable passivated layer). Compared with fresh NCM811, the initial cycle of ambient-air-exposed (aging time: 1 month) NCM811 presents lower Coulombic efficiency (CE%) and an abnormal potential polarization during the initial charging state (Figure a), which is assigned as a classic electrochemical phenomenon for air-exposure-induced Li 2 CO 3 accumulation on the NCM cathode .…”
Section: Tms Quantification Of Native Carbonate Derived From Ambient-...mentioning
confidence: 99%